Experiences of women discharged less than 24 hours post vaginal birth: a systematic review protocol. (November 2017) - Cusack, Lynette; Smith, Morgan Roberta
Abstract : Review question: The objective of this qualitative review is to synthesize the best available evidence on the meaning of early hospital discharge for women following a normal vaginal birth.